Proteogenomic insight into the basis of the insecticide tolerance/resistance of the pollen beetle Brassicogethes (Meligethes) aeneus - Kocourek, Frantisek; Stara, Jitka; Sopko, Bruno; Talacko, Pavel; Harant, Karel; Hovorka, Tomas; Erban, Tomas (Journal of proteomics, 2021)
The pollen beetle is a major pest of oilseed rape. Although various resistance mechanisms have been identified, such as kdr (mutation in the sodium channel) and metabolic resistance (CYP overexpression), other "hidden" factors also exist. Some studies have stressed the importance of epistasis as a genetic background. The combination of kdr and metabolic resistance appears to be unfavorable under field conditions in the absence of pesticide selection. The regulation of detoxification enzymes can play an important role, but we highlight different detoxification markers compared to those emphasized in other studies. We also stress the importance of studying the role of markers identified as pathogenesis-related protein 5-like (PR5; upregulated by insecticides) and highlight the role of RNA (DEAD-box) helicases (downregulated by insecticides). Thus, we suggest the importance of epigenetic drivers of resistance/tolerance to pesticides. The key results are similar to those of our previous study, in which deltamethrin treatment of the pollen beetle was also investigated by a proteogenomic approach. Indeed, the mechanism leading to resistance of the pollen beetle may be an innate mechanism that the pollen beetle can also employ in natural habitats, but under field conditions (pesticide exposure), this mechanism is used to survive in response to insecticides. SIGNIFICANCE: Pesticide resistance is a serious problem that hampers the successful production of crops. Understanding the mechanisms of insecticide resistance is highly important for successful pest control, especially when considering integrated pest management. Here, using a proteogenomic approach, we identified novel markers for understanding pollen beetle resistance to pesticides. In addition, future studies will reveal the role of these markers in the multiresistance of pollen beetle populations. We highlight that the proteins identified as PR5, which are known to occur in beetles and are similar to those in plants, may be responsible for tolerance to multiple stresses. In addition, our results indicate that the RNA helicases that exhibited changes in expression may be the epigenetic drivers of multiresistance. The nature of these changes remains an open question, and their relevance in different situations (responses to different stresses) in natural habitats in the absence of pesticides can be proposed.
Keywords: brouci; Thiacloprid; Pollen; Deltamethrin; proteogenomika; Insecticides; pyl; Proteogenomics; Label-free proteomics; pyrethriny; zvířata; Coleoptera; Multiresistance; Epigenetics; lambda-cyhalothrin; insekticidy; Insecticide Resistance; Pyrethrins; rezistence k insekticidům; Animals